Segmentation Of Stretched Pap Smear Cytology Images Using Clustering Algorithm. - Ghafar, R; Mat Isa, N A; Ngah, U K; Mashor, M Y; Othman, N H (2003)

(untitled)
Papanicolaou test or better known as Pap test is the most popular and effective screening test for cervical cancer. At time, however, the detection of abnormal or cancerous cervical cells can be missed due to technical and human errors.